Epidurinės seromos, susidariusios atlikus kranioplastiką, gydymo iššūkiai: atvejo analizė ir literatūros apžvalga - Žalalytė, Živilė; Šustickas, Gytis (Lietuvos chirurgija, 2022)
Cranioplasty has its risks and complications as all surgical procedures. Treatment of complications are poorly known and could raise significant challenges. One of these complications is epidural fluid collection (EFC). We presented a case of recurrence EFC with deterioration of consciousness. A decompressive craniectomy was performed after rotten subdural hematoma and craniectomy so a cranioplasty was done after more than a half year of cured infection. An EFC occurred next day and one month after the cranioplasty. Due to many repetitive surgeries and head computed tomography scans a vacuum drainage system was formed. After twelve days of treatment the patient improved and the EDC disappeared with this system. We tried to search possible causes and treatment methods for EFC in literature. However, the pathogenesis is still unknown and treatment is only symptomatic.